Carvacrol Conjugated Zinc Oxide Nanoparticles as Prospective Agents against Clinically Isolated Carbapenem Resistant Acinetobacter Species (Medical Forum Monthly, 2022)
Objective: To evaluate the antibacterial activity of Carvacrol conjugated zinc oxide nanoparticles against Carbapenem resistant Acinetobacter isolates and to assess its combination with meropenem.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at the Dr Ziauddin Hospital, North Campus, Karachi from February, 2021 to January, 2022.Materials and Methods: The study was conducted on 50 Carbapenem resistant Acinetobacter isolates. The study was approved by ethics review committee (ERC) reference code: 2971220SHPHA. Minimum inhibitory concentration of Carvacrol zinc oxide nanoparticles was determined using broth macrodilution method on 5 isolates and the concentration which inhibited bacterial growth was noted. Agar well diffusion method was then performed on 50 isolates to observe zone of inhibition of the compound at observed MIC. Colistin was used as a standard drug. Checker board assay was done to explore type of interaction between Carvacrol zinc oxide nanoparticles and meropenem. Inter-group comparison was done using Kruskal wallis ANOVA and p-value of less than 0.05 was considered statistically significant.Results: The minimum concentration of Carvacrol zinc oxide nanoparticles which inhibited bacterial growth was found to be 0.04mg/ml against all the isolates. Zone of inhibition on agar well diffusion was found to be in the range of 20-30mm as compared to colistin (0-14mm) and meropenem (0mm) with p-value being 0.00. Additive interaction was found between carvacrol zinc oxide nanoparticles and meropenem with FICI of 1.5.Conclusion: This study brings forth anti- bacterial activity of a new compound that in future can be helpful for new antibiotic development.